2014
DOI: 10.1089/tmj.2013.0318
|View full text |Cite
|
Sign up to set email alerts
|

Support for e-Health Services Among Elderly Primary Care Patients

Abstract: Background: E-health has a substantial potential to improve access to as well as support efficient and effective care for the elderly. Questions remain and must be addressed, however, regarding the challenges faced by the elderly in the use of this technology. The aim of the study was to assess the attitude (needs) and preferences of the elderly in a selected region of Poland regarding selected e-health services and the factors associated with them. Materials and Methods: The study was conducted among 286 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
79
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 29 publications
7
79
0
11
Order By: Relevance
“…64,65 The undeniable advantage is also the involvement of seniors in the process of treatment and rehabilitation and improvement of their health awareness. Patients who do well in a telecare program may not need to come in for their next regularly scheduled in-person visit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 The undeniable advantage is also the involvement of seniors in the process of treatment and rehabilitation and improvement of their health awareness. Patients who do well in a telecare program may not need to come in for their next regularly scheduled in-person visit.…”
mentioning
confidence: 99%
“…If the system is given a chance to fit into the everyday lifestyle of the elderly, giving them a sense of security and at the same time allowing them to lead a more independent life, its acceptance will increase significantly. 25,69,89 A study performed by Bujnowska and Pirogowicz 64 showed that approximately 41% of the elderly had a favorable attitude toward e-health services and were willing to use it if/when offered an opportunity to do so. A substantial majority (84%) of supporters expressed a desire to receive simple medical recommendations via mobile phone or a computer, although significant majorities (61% and 60%, respectively) wanted to receive the results of tests by email or SMS reminders for scheduled visits or prescribed medications.…”
mentioning
confidence: 99%
“…Similar to the previous work, in [24] is presented a case of study to assess the willingness to use information systems among 286 patients over 60 years register in southwest Poland's Lower Silesia Province. This questionnaire asks about the current usage of information technologies by the patients, and their willingness of usage of services based on this kind of technologies.…”
Section: Statistics and Impactmentioning
confidence: 94%
“…At present there are several definitions of the e-health concept (Bujnowska-Fedak & Pirogowicz, 2014;Oh, Rizo, Enkinit & Alejandro, 2005). E-health can be defined as the use of information and communication technologies, particularly the Internet, to enable healthcare and improve people' health.…”
Section: E-healthmentioning
confidence: 99%
“…E-health can have different forms such as electronic health records, electronic prescriptions, clinical decision support, telemedicine, mHealth, or consumer health informatics (EHealth, 2015). As Bujnowska-Fedak & Pirogowicz (2014) claim, e-health technological devices can increase access to healthcare, cut healthcare and administration costs, reduce patient's visits at the doctor, provide a complex overview of patient's state of health, raise information exchange, and improve public and individual health by personalized medical approach. E-health technologies are nowadays on their rise since they can help to overcome geographical barriers between the patient and the healthcare provider and address specific patient's needs.…”
Section: E-healthmentioning
confidence: 99%